The Effect of Interest Rate and Inflation on Forex Rates - Sofyanto Hadi (Universitas Trisakti, 2005)
The purpose of this study is to do the simulation by using arbitrage facilities for such investment of foreign exchange. This study will find the best foreign exchange between US Dollar, SGD,CAD and Yen, with the best interest rate and the best inflation rate for such transaction by using arbitrage transaction mechanism. In forex transaction, the risk of speculation is very high but this is becoming a reason why this kind of transaction was being attractive and obviously more economic players have an opportunity to get more profit due to differences occurred (spread) on exchange rates. The problem is how to manage such situation the most possible way, especially for managers. The role of estimation, for example by knowing the variables that determined foreign exchange rates, is getting more important in forex trading. Beside that, arbitrage can give additional profit from a forex investment and windfall profit from the spread of the foreign exchange.